High Precision Leaf Instance Segmentation for Phenotyping in Point Clouds Obtained Under Real Field Conditions - Marks, Elias; Sodano, Matteo; Magistri, Federico; Wiesmann, Louis; Desai, Dhagash; Marcuzzi, Rodrigo; Behley, Jens; Stachniss, Cyrill (IEEE robotics and automation letters, 2023)
Measuring plant traits with high throughput allows breeders to monitor and select the best cultivars for subsequent breeding generations. This can enable farmers to improve yield to produce more food, feed, and fiber. Current breeding practices involve extracting leaf parameters on a small subset of the leaves present in the breeding plots, while still requiring substantial manual labor. To automate this process, an important step is the precise distinction between separate leaves, which is the problem we address in this letter. We exploit recent advancements in 3D deep learning to build a convolutional neural network that learns to segment individual leaves. As done in current breeding practices, we select a subset of leaves to be used for phenotypic trait evaluation as this allows us to alleviate the influence of segmentation errors on the phenotypic trait estimation. To this extent we propose to use an additional neural network to predict the quality of each segmented leaf and discard inaccurate leaf instances. The experiments show that our network yields higher segmentation accuracy on sugar beet breeding plots planted under the supervision of the German Federal Office for Plant Varieties. Furthermore, we show that our neural network helps in filtering out leaves with lower segmentation accuracy.